Hubungan kecemasan dental anak umur 7-11 tahun dengan indeks karies di SD Negeri 27 Pemecutan Denpasar Barat - Putu Fenti Surya Pratami; Mia Ayustina Prasetya; Adijanti Marheni (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Early routine check up to dentist was one of the caries preventive measures, however there are still many people ignore about dental health and mouth because they feel anxious or fear of it. Method: This research is an analytic research by doing cross sectional approach. The respondent in this research are 95 children among 7-11 years at SD Negeri 27 Pemecutan in West Denpasar in 2016/2017 period. The samples was taken by using the stratified random sampling technique with the questioner entitled Children’s Fear Survey Schedule-Dental Subscale (CFSS-DS) as the measuring instrument which were already translated into Bahasa Indonesia and caries index to count the number of caries. Results: The result of this research shows that the respondent who had anxiety has DMF-T index with the higher median which is 2 with the interquartile range at 3 than other respondent who had no anxiety which is 0 with the interquartile range at 3 and that means statistically (p= 0.022). The respondent who had anxiety has def-t index with the higher median which is 5 with the interquartile range at 5 than the respondent who had no anxiety which the median is 2 with the interquartile range at 5 and that means statistically (p=0.001). Conclusion: Based on the result of this research, the writer can conclude that there is a relation which is significant with the children dental anxiety among 7-11 years with the caries index at SD Negeri 27 Pemecutan in West Denpasar.